"When did you see it?" The effect of emotional valence on temporal source memory in aging. Issue 5 (4th July 2022) - Ceccato, Irene; La Malva, Pasquale; Di Crosta, Adolfo; Palumbo, Rocco; Gatti, Matteo; Momi, Davide; Logrieco, Maria Grazia Mada; Fasolo, Mirco; Mammarella, Nicola; Borella, Erika; Di Domenico, Alberto
ABSTRACT: Previous studies consistently showed age-related differences in temporal judgment and temporal memory. Importantly, emotional valence plays a crucial role in older adults' information processing. In this study, we examined the effects of emotions at the intersection between time and memory, analysing age-related differences in a temporal source memory task. Twenty-five younger adults (age range 18–35), 25 old adults (age range 65–74), and 25 old–old adults (age range 75–84) saw a series of emotional pictures in three sessions separated by a one-day rest period. In the fourth session, participants were asked to indicate in which session (1, 2, or 3) they saw each picture. Results showed that old–old adults tended to collocate negative pictures distant in time, while positive stimuli were remembered as more recent than real, compared to neutral pictures. To a lower extent, people over 65 showed the same pattern of results. In contrast, emotional valence did not affect younger adults' temporal positioning of stimuli. Current findings fit well with the Socio-Emotional Selectivity Theory's assumptions and extended the literature on the positivity effect to temporal source memory.